Retail Store Segmentation for Target Marketing - ÇAKIR, ÖZGÜR (SPRINGER-VERLAG BERLIN, 2015)
In this paper, we use Data Mining techniques such as clustering and association rules, for the purpose of target marketing strategy. Our goal is to develop a methodology for retailers on how to segment their stores based on multiple data sources and how to create marketing strategies for each segment rather than mass marketing. We have analyzed a supermarket chain company, which has 73 stores located in the Istanbul area in Turkey. First, stores are segmented in 5 clusters using a hierarchical clustering method and then association rules are applied for each cluster.
Keywords: Clustering; Association rules; Market basket analysis; Segmentation; STRATEGIES